Sociolinguistic census in the province of Cajatambo - Solís Fonseca, Gustavo (1999)
The data in this article come from a sociolinguistic census carried out in the province of Cajatambo in 1987. From what is published here we want to highlight the aspect of knowledge and use of languages in the district of Cajatambo, capital of the province of the same name, which includes the neighborhoods of Antay and Tambo. These two neighborhoods appear to be formed by very important social formations to evaluate the sociolinguistic relations of their members, since they are divided into Antay Indio and Antay Mozo; and Tambo Indio and Tambo Mozo.